2017
DOI: 10.1371/journal.pone.0173105
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal activity, vector relationships and genetic analysis of mosquito-borne Stratford virus

Abstract: There are many gaps to be filled in our understanding of mosquito-borne viruses, their relationships with vectors and reservoir hosts, and the environmental drivers of seasonal activity. Stratford virus (STRV) belongs to the genus Flavivirus and has been isolated from mosquitoes and infected humans in Australia but little is known of its vector and reservoir host associations. A total of 43 isolates of STRV from mosquitoes collected in New South Wales between 1995 and 2013 was examined to determine the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…Stratford virus (STRV) RNA was detected in an isolate of Anopheles annulipes collected in Australia from 1995–2013 [ 54 ]. Sequence analysis based on part of the NS5 gene sequence displayed 95–99% homology among the different isolates of STRV, and 2% divergence was detected between the isolates collected in 1995–2013 and the first isolates of 1961.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stratford virus (STRV) RNA was detected in an isolate of Anopheles annulipes collected in Australia from 1995–2013 [ 54 ]. Sequence analysis based on part of the NS5 gene sequence displayed 95–99% homology among the different isolates of STRV, and 2% divergence was detected between the isolates collected in 1995–2013 and the first isolates of 1961.…”
Section: Resultsmentioning
confidence: 99%
“…The main vector of STRV is thought to be Aedes spp., without important contribution by Culex spp. [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…notoscriptus , Aedes procax , and Ae. vigilax ) and Anopheles annulipes [ 63 ]. STRV was first isolated in Ae.…”
Section: Kokobera and Related Virusesmentioning
confidence: 99%
“…This cDNA clone can infect the brain cells in mice and it can also infect the Aedes mosquito; thus, it is a useful tool to study the virus transmission, related diseases and research suitable therapeutics [80]. Like dengue virus, model studies suggested that there are chances that it will spread throughout the world [81,82] and it may be possible to spread along with other flaviviruses like dengue, West Nile virus, chikungunya and Stratford virus due to the common vector Aedes [83,84].…”
Section: Current Scientific Progressmentioning
confidence: 99%